Overview of Knowledge about the Causes of Halitosis and Its Treatment in Society (Literature Review Study) - Zulkarnain; Nur Fatimatul Usra; Hadijah Alimuddin; Aisyah AR (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2023)
Halitosis is an oral health condition characterized by continuous unpleasant breath odour. The causes of halitosis can be of both intraoral and extraoral origin. Public knowledge about halitosis is needed because it can help in preventing and dealing with halitosis. The purpose of this study is to find out an overview of public knowledge about the causes and treatment of halitosis. This research uses the literature study method, namely the method of collecting library data, reading and recording, and managing research materials. Based on the results of literature reviews in 8 journals, it can be concluded that the picture of knowledge about halitosis and its treatment in the community is relatively moderate. People know that halitosis is a poor oral health condition characterized by an unpleasant breath odour. People know that halitosis comes from poor oral hygiene as well as systemic diseases, halitosis can be treated by brushing your teeth, consuming fresh fruit and using mouthwash.